Extraction current transients for mobility determination—A comparative study - Staffan Dahlström; Christian Ahläng; Kim Björkström; Sofia Forsblom; Benjamin Granroth; Kaj Jansson; Axel Luukkonen; Muhammad Talha Masood; Julie Poulizac; Syeda Qudsia; Mathias Nyman (AIP Advances, 2020)
In this work, we measure the hole mobility in the model polymer system poly(3-hexylthiophene-2,5-diyl) by using different measurement techniques. Our main purpose is to determine how the recently developed charge extraction by a linearly increasing voltage technique for metal–insulator–metal devices (MIM-CELIV) compares to other commonly used methods, such as space charge limited currents and time-of-flight. Our findings suggest that the MIM-CELIV technique gives a slightly lower mobility than the other techniques, which is understandable given that the method measures the mobility of relaxed charge carriers in the dark unlike, for example, time-of-flight where charge carriers are photogenerated. In addition, we scrutinize the accuracy and reliability of the techniques used, showing that differences in mobility smaller than a factor of two are not detectable unless statistics from many devices are available.